Singlet oxygen generation properties of an inclusion complex of cyclic free-base porphyrin dimer and fullerene C60. Issue 30 (28th March 2017) - Ooyama, Yousuke; Enoki, Toshiaki; Ohshita, Joji; Kamimura, Takuya; Ozako, Shuwa; Koide, Taro; Tani, Fumito
Abstract : We demonstrate that a cyclic free-base porphyrin dimer and its inclusion complex with fullerene C60 possess the ability to generate singlet oxygen ( 1 O2 ) under visible light irradiation. Abstract : To gain insight into the singlet oxygen ( 1 O2 ) generation properties of supramolecular complexes of cyclic free-base porphyrin dimer with fullerene C60, we evaluated the 1 O2 quantum yield ( Φ Δ ) and rate constant ( K obs ) of 1 O2 generation for a cyclic free-base porphyrin dimer (CPD ) linked by butadiyne bearing four 4-pyridyl groups and its inclusion complex (C60 ⊂CPD ) with C60 . We demonstrate thatCPD andC60 ⊂CPD possess the ability to generate 1 O2 under visible light irradiation. Moreover, it was found that the Φ Δ value ofC60 ⊂CPD is lower than that ofCPD . Based on the kinetic and thermodynamic consideration concerning the electron transfer processes between the porphyrin dimer and C60, this work revealed that the lower Φ Δ value of the C60 inclusion complex would be attributed to the formation of the charge-separated statec 60 ·− -CPD ·+, leading to a low intersystem crossing (ISC) efficiency for the formation of the triplet excited state 3 (CPD)* .